A novel nomogram for predicting the implementation of ultra-fast-track cardiac anesthesia for minimally invasive cardiac surgery - Tian Jiang; Linting Xu; Haozhou Wang; Qinghui Zheng; Yihui Zhang; Jinchen Guo; Xiaokan Lou; Hanwei Wei; Meijuan Yan (Scientific Reports)
Abstract Ultra-fast-track cardiac anesthesia (UFTCA) is a crucial component of enhanced recovery after cardiac surgery (ERACS). However, research on the factors influencing UFTCA implementation remains limited. This study aimed to identify predictors of UFTCA in right-thoracoscopic minimally invasive cardiac surgery (MICS) and develop a nomogram to predict UFTCA implementation. This retrospective study enrolled 947 patients who underwent right-thoracoscopic MICS from January 2021 to July 2023. Patients were randomly divided into derivation (70%) and validation (30%) cohorts. Univariable logistic regression analysis was used for variable selection, followed by a multivariable logistic regression model to determine significant predictors and construct a nomogram for predicting UFTCA implementation. The model’s discrimination, calibration, and clinical effectiveness were evaluated using the validation cohort. Multivariate analysis identified six independent predictors of UFTCA implementation: operation type, fascial plane chest wall blocks (FPCWB), intraoperative sufentanil and dexamethasone dosage, operation later than 8 p.m., and cardiopulmonary bypass (CPB) duration. The nomogram demonstrated good discriminative ability, with areas under the receiver operating characteristic (ROC) curve of 0.869 and 0.862 for the derivation and validation sets, respectively. The calibration plot showed close alignment with the ideal diagonal line, and the decision curve analysis (DCA) confirmed the model’s clinical practical significance. This study developed and validated a nomogram that could predict the implementation of UFTCA in patients undergoing MICS. The nomogram showed that more complexity of procedures, especially multiple valve surgery, higher doses of sufentanil, longer CPB duration and operation later than 8 p.m. were disadvantageous to UFTCA implementation, while administration of dexamethasone and FPCWB were beneficial for UFTCA.